Sistema de gestión técnica de riesgos laborales en el área de producción de la empresa agua purificada y envasa SUPER 33 4x4 - Diaz Hidalgo, Laxon Michael (2018)
In the present research work of the technical management system of occupational hazards is focused on the production area of the Super 33 4x4 purifier and water bottler which is located in the canton Ventanas-Gramalote enclosure in order to establish Preventive procedures in activities that present an unacceptable level of risk and thus improve working conditions. An initial identification was started to determine the existence of the different risk factors using the matrix ICONTEC GTC 45 valuing and weighting each one of them, then used different evaluative methods such as REBA for the Inadequate postures, GINSHT used in the valuation of manual handling of loads, the Check List okra employed for repetitive movements and WILLIAM FINE in the mechanical risks, having as results by means of these evaluations levels of risks which leads to an improvement of the jobs to carry out the activities in an accident-free environment. Through this need to exercise labour in accident-free jobs, comprehensive operational controls are posed for the prevention of risks in each activities with the necessary intervention, predominating in the source of danger, the means of transmission and the individual.